The Shaping of Future Sustainable Energy Policy in Management Areas of Indonesia's Energy Transition - Fatma Ulfatun Najicha; Mukhlishin Mukhlishin; Supiandi Supiandi; Saparwadi Saparwadi; Dinil Abrar Sulthani (Lembaga Contrarius Indonesia, 2023)
Modifications to energy management models have made them more adaptable and dynamic, with intelligent monitoring and control of energy production, distribution, storage, and consumption. However, the management paradigm has not yet been optimally implemented, given that fossil fuels account for 73% of all greenhouse gas (GHG) emissions in the energy sector. The purpose of this study was to find out the policy of management area in energy transition toward sustainable development. This was normative legal research employing the statutory approach, the fact approach, and the case approach. The results indicate that a global energy transition will have a positive effect on the future stability and development of economies worldwide. Therefore, the green investment promotion for Renewable energy has acquired prominence in recent years and is now at the forefront of global efforts to reform the energy sector. In addition, the harmonization of legislation and technical requirements is highlighted as a requirement for achieving this objective.